Strong spin-filtering and spin-valve effects in a molecular V–C60–V contact - Koleini, Mohammad; Brandbyge, Mads (Beilstein Journal of Nanotechnology, 2012)
Motivated by the recent achievements in the manipulation of C60 molecules in STM experiments, we study theoretically the structure and electronic properties of a C60 molecule in an STM tunneljunction with a magnetic tip and magnetic adatom on a Cu(111) surface using first-principles calculations. For the case of a vanadium tip/adatom, we demonstrate how spin coupling between the magnetic V atoms, mediated by the C60, can be observed in the electronic transport, which display a strong spin-filtering effect, allowing mainly majority-spin electrons to pass (>95%). Moreover, we find a significant change in the conductance between parallel and anti-parallel spin polarizations in the junction (86%) which suggests that STM experiments should be able to characterize the magnetism and spin coupling for these systems.
Keywords: fullerene; molecular spintronics; scanning tunneling microscopy; spin transport